HIF-1α limits myocardial infarction by promoting mitophagy in mouse hearts adapted to chronic hypoxia - Alanova, Petra; Alan, Lukas; Opletalova, Barbora; Bohuslavova, Romana; Abaffy, Pavel; Matějková, Kateřina; Holzerova, Kristyna; Benák, Daniel; Kaludercic, Nina; Menabo, Roberta; Di Lisa, Fabio; Ostadal, Bohuslav; et al. (Acta physiologica (Oxford, England), 2024)
AIM: The transcriptional factor HIF-1α is recognized for its contribution to cardioprotection against acute ischemia/reperfusion injury. Adaptation to chronic hypoxia (CH) is known to stabilize HIF-1α and increase myocardial ischemic tolerance. However, the precise role of HIF-1α in mediating the protective effect remains incompletely understood. METHODS: Male wild-type (WT) mice and mice with partial Hif1a deficiency (hif1a +/-) were exposed to CH for 4 weeks, while their respective controls were kept under normoxic conditions. Subsequently, their isolated perfused hearts were subjected to ischemia/reperfusion to determine infarct size, while RNA-sequencing of isolated cardiomyocytes was performed. Mitochondrial respiration was measured to evaluate mitochondrial function, and western blots were performed to assess mitophagy. RESULTS: We demonstrated enhanced ischemic tolerance in WT mice induced by adaptation to CH compared with their normoxic controls and chronically hypoxic hif1a +/- mice. Through cardiomyocyte bulk mRNA sequencing analysis, we unveiled significant reprogramming of cardiomyocytes induced by CH emphasizing mitochondrial processes. CH reduced mitochondrial content and respiration and altered mitochondrial ultrastructure. Notably, the reduced mitochondrial content correlated with enhanced autophagosome formation exclusively in chronically hypoxic WT mice, supported by an increase in the LC3-II/LC3-I ratio, expression of PINK1, and degradation of SQSTM1/p62. Furthermore, pretreatment with the mitochondrial division inhibitor (mdivi-1) abolished the infarct size-limiting effect of CH in WT mice, highlighting the key role of mitophagy in CH-induced cardioprotection. CONCLUSION: These findings provide new insights into the contribution of HIF-1α to cardiomyocyte survival during acute ischemia/reperfusion injury by activating the selective autophagy pathway.
Keywords: Myocytes, Cardiac; Hypoxia-Inducible Factor 1, alpha Subunit; Mice; zvířata; Mitophagy; Hypoxia; hypoxie; mužské pohlaví; fyziologická adaptace; kardiomyocyty; mitofagie; Myocardial Infarction; myši; Animals; infarkt myokardu; Mice, Inbred C57BL; faktor 1 indukovatelný hypoxií - podjednotka alfa; Male; Adaptation, Physiological; myši inbrední C57BL